Profile and Evaluation of Dermatophytosis - Ardhiah Iswanda Putri; Linda Astari (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Dermatophytosis is an infection of the tissues, for example, the stratum corneum of the epidermis, hair, and nails, which is caused by dermatophyte fungi group. This retrospective study has never been done before and the 2011-2013 election was conducted due to changes in the health insurance system at RSUD Dr. Soetomo. Purpose: To evaluated patient management of dermatophytosis in Mycology Division Outpatient Clinic Dr. Soetomo General Hospital 2011-2013. Methods: A descriptive retrospective study the aim to evaluated general description, epidemiology, clinical manifestation, establisment diagnosis, management and repeated control new patient dermatophytosis. Results: Percentage new case  dermatophytes infection increased, but the number of visits to URJ for 3 years decreased. The most diagnosis is  tinea corporis. Most cases come from Surabaya. The most patient complaints are itching. The most efflorescence is polycyclic. Griseofulvin is the most therapeutic choice given in the case of tinea corporis. Conclusions: In this study most cases of dermatophytosis is tinea korporis. The diagnosis approach of dermatophytosis diagnosis was obtained by anamnesis, physical examination, and additional examination. Most of dermatophytosis  treated with antifungal griseofulvin.